Attitude and prevalence of early sexual debut and associated risk sexual behavior among adolescents in Tanzania; Evidence from baseline data in a Randomized Controlled Trial - Walter C. Millanzi; Kalafunja M. Osaki; Stephen M. Kibusi (BMC, 2023)
Abstract Background Unsafe sexual behaviours and associated sexual ideas among adolescents may contribute to adverse health consequences for sexual health in adulthood. The patterns of sexual ideology and sociodemographic factors profiles on adolescents' sexual behaviours have not been the subject of a definite consensus in research. The purpose of this study was to investigate the attitude and prevalence of early sexual debut and associated risk sexual behavior among adolescents in Tanzania as the evidence from baseline data in a Randomized Controlled Trial. Methods The study included 647 randomly chosen in-school adolescents from Tanzania and used an analytical cross-section survey in a quantitative research approach. Sexual-risk Behaviour Beliefs and Self-esteem Scale from previous studies were the main data collection tool. According to the Statistical Analysis Software (SAS), computer software version 9.4 descriptive analysis established respondents' socio-demographic profiles, attitudes, prevalence, and determinants linked to teenagers' early sexual debut. The link between the variables was established via multivariate logistic regression at a 5% significance level and a 95% confidence interval. Results The mean age was 15 ± 1.869 years while 57.5% of adolescents were females. 69.7% of adolescents were sexually active whereas 44.8% of them practised sexual behaviours willingly against 24.9% who practised coerced sexual behaviours. The majority (44.4%) and 16.2% of them initiated sexual behaviours during the early and middle adolescence stages respectively. Most adolescents had the ideology that sex was okay to them even before the age of 18 years. Their odds of practicing sexual behaviours were significantly high with the ideology that sex was okay to them even before 18 years of age (AOR = 1.293; p < 0.05; 95%CI: 0.689, 2.989), exposure to drug abuse (AOR = 1.210; p < 0.05; 95%CI: 0.803, 2.130), using media (AOR = 1.006; p < 0.05; 95%CI: 0.748, 2.667) and/or exposure to social groups [Jogging, Gym, health clubs, betting, Games] (AOR = 1.032; p < 0.05; 95%CI: 0.889, 2.044). Conclusion Findings suggest that holding a positive attitude towards early sexual debut is a precursor to early sexual activity among adolescents. Unsafe sex, coercive sex, and other risky sexual behaviors are not uncommon among adolescents starting sex before the age of 18 years. Exposure to drug abuse, online sexual content, and/or social groups significantly influenced early sexual debut irrespective of other known factors. Age-appropriate school-based sexuality education programs should be promoted and implemented to address the most prevalent positive attitude towards early sexual debut and associated risk sexual behaviour among adolescents in Tanzania and other similar settings.